Evaluation of cell disruption for partial isolation of intracellular pyruvate decarboxylase enzyme by silver nanoparticles method - J. Tangtua (2018)
© 2015 Akadémiai Kiadó, Budapest. Candida tropicalis TISTR 5350 was used in the comparison of seven concentration levels of silver nanoparticles (0, 5, 10, 15, 20, 25, and 30 μg ml-1) for cell disruption methods. The optimized cell disruption strategy was selected based on the optimal protein yield and biological activity. The maximum volumetric and specifi c pyruvate decarboxylase (PDC, EC 4.1.1.1) activities (0.53±0.05 U ml-1 and 0.17±0.02 U mg-1 protein, respectively) were observed at 15 μg ml-1 silver nanoparticles. The silver nanoparticle concentration level of 15 μg ml-1 was investigated further by comparing the reaction mixtures at different time intervals of 0, 1, 2, 3, 4, 5, and 6 min. The result showed that the highest specifi c PDC activity of 0.39±0.01 U mg-1 protein was obtained from mixing for 3 min. This was not significantly different (P≤0.05) from other mixing time intervals.